Choral of University of Havana: sociocultural practices of an octogenarian institution (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
This article exposes the results of an investigation that covers the last two decades of the musical activity of the University Choir of the University of Havana (1995-2017). Through empirical methods such as observation, documentary review and systematization of experiences, the analysis, description and characterization of their actions were carried out within the university extension process of the University of Havana. As results, the peculiarities of the musical activity carried out by this octogenarian group, the oldest of its kind in activity in the country, are shown. As practical contributions, a unified information platform of the artistic presentations made in this period was formed, which were grouped into typologies, that allow a quick search to be carried out within the different facets or areas of its activity. In addition, the SWOT matrix was obtained, whose results become central axes for new investigations of their artistic practices and for the design of strategies to promote their sociocultural activity.
Keywords: University choir; university musical activity; university extension; integral formation